Predominantly hemorrhagic choroidal neovascular lesion from exsudative age-related macular degeneration treated with intravitreal ranibizumab therapy - Amaro,Miguel Hage (2013)
The authors relate a predominantly hemorrhagic choroidal neovascular lesion from neovascular. Age-related macular degeneration patient case treated with intravitreal ranibizumab therapy. Monthly ranibizumab (six intravitreal injections) displayed a promising response but this limited report is insufficient to guarantee the indication for all predominantly hemorrhagic choroidal neovascular lesion from neovascular age-related macular degeneration. Further studies will be necessary for complete validation of our results for all predominantly hemorrhagic choroidal neovascular lesions from CNV due to AMD.